Impact of landfill fly ash on soil contamination with heavy metals in Rabigh Area, Saudi Arabia: Impact of landfill fly ash - Samir G. M., Al-Solaimani; Mousa, ’magdi; Ibrahim, Moar; Zaki Hindi, Sherif S.; A-Qureshi, Abdul-Rahman (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2024)
This study was carried out to investigate special distribution of micro- and toxic-elements separated from carbon fly ash buried in landfill in Rabigh, Saudi Arabia. The highest total and DTPA extractable and available concentrations of sulfur (S), manganese (Mn), zinc (Zn), copper (Cu), iron (Fe), aluminum (AL), cobalt (CO), chromium (Cr), nickel (Ni) , vanadium (V) are in the soil inside the landfill, then concentrations decrease with increase in distances 0, 250, 500, 1000 m away from landfill at all locations, north south, east, west. The soil total micro-and toxic-element accumulations are highest at south location, followed by east, then west and the least concentrations are in the soil of the north location. The soil DTPA extractable available micro- and toxic-elements are highest at the east location, then south then north and west location has soil with the least element concentrations. Iron (Fe) as soil total micro-element is the highest (38888.37 mg/kg), but as DTPA available element it is very low (16.46 mg/kg) at all locations and distances. Sulfur (S) comes second to Fe as total soil element with (541.24 mg/kg), then Mn element, while for soil DTPA available micro-elements S is the highest element (193.60 mg/kg) followed by Fe, and Cu is the element with the least concentrations in the soil. For toxic-elements Al dominates total soil concentrations (19173.27 mg/kg), followed by V then Cr, Ni and Co, and for DTPA available soil metals Ni and V gave higher concentrations than Co and Cr at all distances and locations. The concentration of soil total Fe is higher than European Standards (2002) , Saudi Standards ( 2020 ) and Indian Standards (2000), and that of S is higher than Saudi Standards (2020). Nickel (Ni) is higher than Saudi Standards (2020). The rest metal concentrations in landfill soil are below phototoxic concentration standards put forward by EU (2002), Saudi Arabia (2020), and Indian standards (2000). The rest element concentrations in landfill soil are below phototoxic concentration standards put forward by these standards.